Unit Commitment-Security Constraints Using the Priority List-Genetic Algorithm Method in the IEEE 6 Bus and IEEE 14 BUS Case Studies - Chico Hermanu Brillianto Apribowo; Muhammad Fakhri Erriyanto; Sutrisno Sutrisno; Agus Ramelan (Journal of Electrical, Electronic, Information, and Communication Technology, 2021)
Unit commitment (UC) is the scheduling of on-off operation of a power plant unit to meet the demand for electrical power over a certain period of time in order to obtain an economical total cost of generation The PL method is used for scheduling and the AG is optimized using DOE for ED problems. The results obtained from the research that there are still improvements in the calculation of ED problems using load flow constraints and can be corrected. The results of the comparison of the total percentage cost of IEEE 6 buses used in ED problems without considering the load flow constraints with those considering this problem amounted to 26.30%. The result of the comparison of the total percentage cost of IEEE 14 buses used in ED problems without considering load flow constraints with those considering this problem is 11.55%. The load flow calculation using Newton-Rapshon uses a smaller number of iterations and a shorter time than Gauss-Seidel.